Ecological niches occupied by Dichapetalum cymosum (Hook.) Engl. (Gifblaar) in South African rangeland communities - Truter, Wayne Frederick (University of Pretoria, 2014)
Dissertation (MSc Agric)--University of Pretoria, 2013.